PARADOKS SUMBER DAYA ALAM: PENGARUH DANA BAGI HASIL SUMBER DAYA ALAM, KETIMPANGAN EKONOMI, DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI KAYA SUMBER DAYA ALAM DI INDONESIA - Alifah Putri Eriza; Zulfa Emalia (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to analyze the effect of Natural Resource Revenue Sharing (DBH-SDA), economic inequality measured by the Gini Index, and the Human Development Index (HDI) on economic growth in resource-rich provinces in Indonesia. The phenomenon of the natural resource paradox indicates that abundant natural resources do not necessarily lead to improved welfare. This study employs a quantitative approach using panel data from selected resource-rich provinces during the 2017–2023 period. The analytical method used is panel data regression with a Fixed Effect Model (FEM). The results show that DBH-SDA has no significant effect on economic growth, economic inequality has a negative effect, while HDI has a positive and significant effect on economic growth. These findings suggest that human development plays a more crucial role than natural resource dependence in driving sustainable economic growth.